Pengaruh Praktik MSDM Terhadap Daya Saing Pada Pelaku UMKM (Usaha Mikro Kecil Menengah) Di Dusun Rejoso Desa Junrejo - Maulana, Ramadhani Dika; Pardiman, Pardiman; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The purpose of this research is to see the influence of UMKM practices on the competitiveness of UMKM in Rejoso Hamlet, Junrejo Village. The number of samples used in this research was 35 UMKM, using a probability sampling method in the form of census sampling. The data collection technique used was a questionnaire. Research data was analyzed using IBM SPSS software. Analysis data using multiple regression method. The research results show that recruitment does not have a positive and significant influence on the competitiveness of UMKM in Rejoso Hamlet, Junrejo Village. The training had a positive and significant influence on the competitiveness of MSMEs in Rejoso Hamlet, Junrejo Village. Payroll has a positive and significant influence on the competitiveness of UMKM in Dsusun Rejoso, Junrejo Village. Keywords: Competitiveness, Recruiting, Training, Payroll, UMKM